Targeting Mitochondrial Metabolism to Reverse Radioresistance: An Alternative to Glucose Metabolism - Chenbin Bian; Zhuangzhuang Zheng; Jing Su; Huanhuan Wang; Sitong Chang; Ying Xin; Xin Jiang (MDPI AG, 2022)
Radiotherapy failure and poor tumor prognosis are primarily attributed to radioresistance. Improving the curative effect of radiotherapy and delaying cancer progression have become difficult problems for clinicians. Glucose metabolism has long been regarded as the main metabolic process by which tumor cells meet their bioenergetic and anabolic needs, with the complex interactions between the mitochondria and tumors being ignored. This misconception was not dispelled until the early 2000s; however, the cellular molecules and signaling pathways involved in radioresistance remain incompletely defined. In addition to being a key metabolic site that regulates tumorigenesis, mitochondria can influence the radiation effects of malignancies by controlling redox reactions, participating in oxidative phosphorylation, producing oncometabolites, and triggering apoptosis. Therefore, the mitochondria are promising targets for the development of novel anticancer drugs. In this review, we summarize the internal relationship and related mechanisms between mitochondrial metabolism and cancer radioresistance, thus exploring the possibility of targeting mitochondrial signaling pathways to reverse radiation insensitivity. We suggest that attention should be paid to the potential value of mitochondria in prolonging the survival of cancer patients.